Very-long-chain 3-hydroxy fatty acids, 3-hydroxy fatty acid methyl esters and 2-alkanols from cuticular waxes of Aloe arborescens leaves. (May 2015) - Racovita, Radu C.; Peng, Chen; Awakawa, Takayoshi; Abe, Ikuro; Jetter, Reinhard
Graphical abstract: Leaf waxes of Aloe arborescens were found to contain various aliphatic compound classes in characteristic chain length and isomer distributions. Three homologous series were identified as 3-hydroxy fatty acids and their methyl esters (both mainly C28 ), and 2-alkanols (mainly C31 ). Based on structure similarities and chain length distributions, the biosynthetic pathways leading to these novel wax constituents can be hypothesized. Highlights: 11 compound classes comprising 49 structures were identified and quantified. Homolog/isomer distributions of C42 –C52 alkyl esters were determined by GC–MS. Free 3-hydroxy fatty acids, their methyl esters, and 2-alkanols were identified. The structures suggest biosynthetic pathways intercepting elongation intermediates. Epi- and intracuticular wax mixtures on the adaxial and abaxial sides of the leaf differed. Abstract: The present work aimed at a comprehensive chemical characterization of the cuticular wax mixtures covering leaves of the monocot species Aloe arborescens . The wax mixtures were found to contain typical aliphatic compound classes in characteristic chain length distributions, including alkanes (predominantly C31 ), primary alcohols (predominantly C28 ), aldehydes (predominantly C32 ), fatty acid methyl esters (predominantly C28 ) and fatty acids (bimodal distribution around C32 and C28 ). Alkyl esters ranging from C42 to C52 were identified, and found to mainly contain C28 alcohol linked to C16 –C20 acids. Three other homologous series were identified as 3-hydroxy fatty acids (predominantly C28 ), their methyl esters (predominantly C28 ), and 2-alkanols (predominantly C31 ). Based on structural similarities and homolog distributions, the biosynthetic pathways leading to these novel wax constituents can be hypothesized. Further detailed analyses showed that the A. arborescens leaf was covered with 15 μg/cm 2 wax on its adaxial side and 36 μg/cm 2 on the abaxial side, with 3:2 and 1:1 ratios between epicuticular and intracuticular wax layers on each side, respectively. Terpenoids were found mainly in the intracuticular waxes, whereas very-long-chain alkanes and fatty acids accumulated to relatively high concentrations in the epicuticular wax, hence near the true surface of the leaf.